PEMANFAATAN TONG SAMPAH ORGANIK MENGATASI SAMPAH DI CIBIRU ASRI CIBIRU WETAN BANDUNG - Susilawati, Elis; Hartini, Ni Nyoman Sri Mas; Supriadi, Dadih; Sutoro, Meylani; Priyadi, Akhmad; Lisni, Ida; Sya’bani, Oktaviani; Amanda, Ruli; Rahmanda, Erin; Wijaya, Youland Friccilia (Gapenas Publisher, 2024)
The community service activity titled